2020
DOI: 10.1016/j.celrep.2020.02.066
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein Rasputin/G3BP Enhances the Stability and Translation of Its Target mRNAs

Abstract: Highlights d In early embryos, the Drosophila G3BP Rasputin (RIN) is polysome associated d RIN binds over 550 mRNAs, which are short, stable, and highly translated d In rin mutants, steady-state levels of its target mRNAs are reduced d Tethering RIN or human G3BPs enhances the expression of a luciferase reporter mRNA

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 99 publications
(148 reference statements)
0
35
0
Order By: Relevance
“…The fact that a treatment of worms with the G3BP2 inhibitor C108 results in a disruption of the circalunar oscillations of erp4.9 provides support for placing it in a pathway with L-Cry and opens the question about possible functions in connection with the circalunar clock. Interestingly, a common feature of the orthologs of both G3BP1/2 and YTHDF1/2/3 are their function in RNA-binding and regulation (33)(34)(35). Furthermore, a screen for interacting proteins of YTHDF1, 2 and 3 in mammalian cells revealed G3BP1 and 2 among the top 25 interacting proteins for each YTHDF (35), suggesting that these proteins can function within a complex.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that a treatment of worms with the G3BP2 inhibitor C108 results in a disruption of the circalunar oscillations of erp4.9 provides support for placing it in a pathway with L-Cry and opens the question about possible functions in connection with the circalunar clock. Interestingly, a common feature of the orthologs of both G3BP1/2 and YTHDF1/2/3 are their function in RNA-binding and regulation (33)(34)(35). Furthermore, a screen for interacting proteins of YTHDF1, 2 and 3 in mammalian cells revealed G3BP1 and 2 among the top 25 interacting proteins for each YTHDF (35), suggesting that these proteins can function within a complex.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions that promote mRNP assembly disrupt Lsm-domain mediated interactions and enable cIDR-driven granule formation (Figure 6). We note that recent work on G3BP has beautifully elaborated phosphorylation-regulated intramolecular interactions that similarly allow the molecule to switch between soluble and assembly competent conformations (Guillén-Boixet et al, 2020; Laver et al, 2020; Sanders et al, 2020). Though our experiments do not yet define molecular and biophysical details by which Atx2 transitions from assembly-inhibited to assembly-competent states, our observations: (a) clearly demonstrate crucial opposing, physiological roles of the Lsm and cIDR domains in this process; and (b) suggest that regulation of intermolecular interactions mediated by the Lsm domain will be involved in control of Atx2-mediated granule assembly.…”
Section: Discussionmentioning
confidence: 92%
“…One possibility is that mRNP remodeling is driven by major conformational changes in RBPs, which not only increase their propensity to drive mRNP condensation, but also result in altered RBP-RBP and RBP-RNA interactions. In this context, recent work on G3BP/Rin has shown that the protein exists in two dramatically different conformational states: a closed form, in which its IDRs are inaccessible for condensation reactions, and a dephosphorylation-induced open form, capable of mediating SG association (Guillén-Boixet et al, 2020; Laver et al, 2020; Sanders et al, 2020). In such a framework, it is easy to see how Atx2 interactions with RBPs and mRNAs could be altered under conditions that support granule assembly.…”
Section: Discussionmentioning
confidence: 99%
“…The target RNA of RBPs is variable, they can bind to different region of mRNA [such as exons, introns, untranslated regions (UTRs)], or interact with other types of RNA, including non-coding RNAs(4), microRNAs, small interference RNAs (siRNA), t-RNAs, small nucleolar RNA (snoR-NA), telomerase RNA, conjugant small nuclear RNA (snRNA) and the RNA part of signal recognition particles (SRP RNA or 7SL RNA(57). These non-coding RNAs form a wide range of secondary structures, which combine with RBP and regulate processes such as RNA splicing, RNA modification(8), protein localization, translation, and maintenance of chromosome stability(9, 10). The functional effects of conventional RBPs depend on the target RNA-RNP complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…The functional effects of conventional RBPs depend on the target RNA-RNP complex formation. Simultaneously, the RNP complex helps RNA processing, translation, export and localization(10, 11).…”
Section: Introductionmentioning
confidence: 99%